β2-adrenergic stress evaluation of coronary endothelial-dependent vasodilator function in mice using 11C-acetate micro-PET imaging of myocardial blood flow and oxidative metabolism - Croteau, Etienne; Renaud, Jennifer M; Archer, Christine; Klein, Ran; DaSilva, Jean N; Ruddy, Terrence D; Beanlands, Rob S; deKemp, Robert A (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Endothelial dysfunction is associated with vascular risk factors such as dyslipidemia, hypertension, and diabetes, leading to coronary atherosclerosis. Sympathetic stress using cold-pressor testing (CPT) has been used to measure coronary endothelial function in humans with positron emission tomography (PET) myocardial blood flow (MBF) imaging, but is not practical in small animal models. This study characterized coronary vasomotor function in mice with [11C]acetate micro-PET measurements of nitric-oxide-mediated endothelial flow reserve (EFRNOM) (adrenergic-stress/rest MBF) and myocardial oxygen consumption (MVO2) using salbutamol β2-adrenergic-activation. Methods [11C]acetate PET MBF was performed at rest + salbutamol (SB 0.2, 1.0 μg/kg/min) and norepinephrine (NE 3.2 μg/kg/min) stress to measure an index of MBF response. β-adrenergic specificity of NE was evaluated by pretreatment with α-adrenergic-antagonist phentolamine (PHE), and β2-selectivity was assessed using SB. Results Adjusting for changes in heart rate × systolic blood pressure product (RPP), the same stress/rest MBF ratio of 1.4 was measured using low-dose SB and NE in normal mice (equivalent to human CPT response). The MBF response was correlated with changes in MVO2 (p = 0.02). Nitric oxide synthase (NOS)-inhibited mice (Ng-nitro-L-arginine methyl ester (L-NAME) pretreatment and endothelial nitric oxide synthase (eNOS) knockout) were used to assess the EFRNOM, in which the low-dose SB- and NE-stress MBF responses were completely blocked (p = 0.02). With high-dose SB-stress, the MBF ratio was reduced by 0.4 following NOS inhibition (p = 0.03). Conclusions Low-dose salbutamol β2-adrenergic-stress [11C]acetate micro-PET imaging can be used to measure coronary-specific EFRNOM in mice and may be suitable for assessment of endothelial dysfunction in small animal models of disease and evaluation of new therapies.